2020
DOI: 10.1007/s43037-020-00073-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultraholomorphic extension theorems in the mixed setting

Abstract: The aim of this work is to generalize the ultraholomorphic extension theorems from V. Thilliez in the weight sequence setting and from the authors in the weight function setting (of Roumieu type) to a mixed framework. Such mixed results have already been known for ultradifferentiable classes and it seems natural that they have ultraholomorphic counterparts. In order to have control on the opening of the sectors in the Riemann surface of the logarithm for which the extension theorems are valid we are introducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Note that in [21, Lemma 5.7] it is shown that for M, N ∈ LC with µ ≤ ν, (M, N ) γ 1 implies (ω M , ω N ) snq (see also [12,Lemma 4,Rem. 6] for r = 1).…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations
“…Note that in [21, Lemma 5.7] it is shown that for M, N ∈ LC with µ ≤ ν, (M, N ) γ 1 implies (ω M , ω N ) snq (see also [12,Lemma 4,Rem. 6] for r = 1).…”
Section: 3mentioning
confidence: 99%
“…The parameter r is then used to introduce the (mixed) growth index γ(•) which measures the opening of the sector under consideration. For more details we refer to [10]- [12] and the references therein.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…( 1.1 ) and ( 1.2 ) are the mixed versions of the standard assumption as on weight functions (denoted by in this work). These types of mixed conditions, for either weight sequences or weight functions, have frequently appeared in the literature in the study of mixed extension results in the ultradifferentiable or ultraholomorphic settings, see [ 3 , 6 , 7 , 10 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main aim of this article is to give a complete solution to ( * * ) and to ( * * ) ′ expressed in terms of growth properties for M. In order to do so, instead of (M {L} ) we consider the weaker requirement 2) are the mixed versions of the standard assumption ω(2t) = O(ω(t)) as t → +∞ on weight functions (denoted by (ω 1 ) in this work). These types of mixed conditions, for either weight sequences or weight functions, have frequently appeared in the literature in the study of mixed extension results in the ultradifferentiable or ultraholomorphic settings, see [3], [16], [6], [7], [10].…”
Section: Introductionmentioning
confidence: 99%